One-Pot Synthesis of Imidazo[2,1-b]thiazole via Groebke–Blackburn–Bienaymé Reaction under Free Catalyts - David Calderón-Rangel; Karla A. González Pérez; Alejandro Corona Díaz; Rocío Gámez-Montaño (Chemistry Proceedings)
The imidazo[2,1-b]thiazole scaffold is widely present in natural and synthetic compounds with important properties or biological activities, such as anti-inflammatory, anti-bacterial, anti-tuberculosis, cytotoxic, anthelmintic, anti-hypertensive, or herbicidal properties. The isocyanide multicomponent reaction (I-MCR) process is a greener alternative and efficient synthetic tool. Herein, we describe a novel methodology, one-pot synthesis for the synthesis of imidazo[2,1-b]thiazole by Groebke–Blackburn–Bienaymé reaction (GBBR) using little-explored 3-formylchromone.